Das Siebenstromland zwischen Bronze- und Früheisenzeit. Eine Regionalstudie - Gass, Anton (Topoi - Berlin Studies of the Ancient World/Topoi - Berliner Studien der Alten Welt, 2016)
The southeastern Land of Seven Rivers (Kazakhstan) - a small region in the Eurasian steppes - shows an enormous concentration of Bronze and early Iron Age archeological monuments, only a small fraction of which have been described by researchers. This study, the first comprehensive investigation of these monuments, also makes an important contribution to knowledge about the historical - cultural evolution of the region.